Homozygosity analysis in a Turkish dementia cohort. (1st February 2022) - Dehghani, Nadia; Guven, Gamze; Beckwell, Jane; Duimstra, Lauren; Gibbons, Elizabeth; Kun‐Rodrigues, Celia; Lisboa, Catarina; Hanagasi, Hasmet; Lohmann, Ebba; Bilgiç, Başar; Samancı, Bedia; Gurvit, Hakan; et al.
Abstract: Background: Diseases caused by homozygous variants are more prevalent in consanguineous populations where regions of homozygosity (ROHs) spanning the genome are extended. The same diseases are comparatively rarer in outbred populations, and thus identifying pathogenic variants is more challenging without much larger cohorts. It has been previously shown that the genomic segment harboring the disease gene is located within the longest ROH more often than expected. Method: We utilize both whole genome genotyping and whole exome sequencing data to identify ROHs and candidate variants causing or contributing to the risk of disease in a consanguineous Turkish dementia cohort. Patient diagnoses in this cohort include Alzheimer's disease, frontotemporal dementia and mild cognitive impairment. Result: Previous studies in consanguineous families from this cohort have identified novel rare biallelic variants in TREM2 as the cause of an atypical frontotemporal dementia phenotype. Additional heterozygous variants in this gene have since been recognized as risk factors for neurodegenerative diseases, most prominently the p.R47H variant is now well established as one of the most significant genetic risk factors for Alzheimer's disease. In this study, we detected homozygous variants within ROHs, in both known neurodegenerative disease‐causing genes, and in novel genes which have been previously implicated in other, rare diseases. These results are important for considering both potential dose‐effects and pleiotropy, respectively. Conclusion: To the best of our knowledge, this is the largest study on the Turkish dementia population which utilizes such extended ROHs to identify rare homozygous variants.